PARTICULARITIES OF MARKETING DECISIONS FOR INNOVATIVE COMPANIES FROM HIGH-TECH INDUSTRY - Lavinia DOVLEAC; Marius BĂLĂŞESCU (Management & Marketing)
This paper highlights the specific way for companies in high tech industry to develop their marketing activity. The companies in this industry are struggling to create and then sell a range of innovative products. High technology products are complex and they enhance a certain level of uncertainty regarding their utility. Due to their novelty (absolute or incremental) the products are accepted by consumers harder than the ordinary consumer products. This paper presents the main results of a qualitative marketing research based on the opinions of managers from high technology industry on specific marketing strategies and tools used to create and launch new products.